PENDEKATAN ANTROPOLOGI LAPANGAN EDWARD EVANS-PRITCHARD DALAM KAJIAN ISLAM - mawardi, Kholid (Fakultas Dakwah IAIN Purwokerto, 2012)
Islam, as a science, shoud be viewed equally as other disciplines. One of the poin isthat other disciplines should be applied as an approach to Islamic studies, since there has beena tense on whether Islam should be studied normatively or historically. Those two approacheshave different assumptions.Considering the development of global knowledge, historical approach in Islamicstudies should be firstly apllied. This means that other disciplines such as sociology,psychology and antropology should be applied in Islamic studies.This article introduces Edward Evans-Pritchard’s Islamic studies with antropologicalapproach which stated that it is necessary to emphasize on the study of religions and primitivebeliefs in its real life and beyond literary and teological texts. One valid theory will explain areligion as it grows in the society, not as perceived by its preachers, so that the power andgrowth of a religion can be reached.